Rose Red Glow:Crossing Borders with Textiles - Pietarinen, Heidi (2025)
Can textiles, like music, painting, sculpture, and architecture, serve as a universal cultural expression that transcends language, nationality, and borders? Examining northern Finnish textile traditions, particularly in a city of Tornio, by the border to Sweden in Finnish Lapland, and Pechenga (Petsamo in Finnish), a historically significant Arctic region on the coast of the Arctic Ocean, reveal the rich entanglement of trade, migration, and international influences. Inspired by Nils Schillmark’s Strawberry Girl (c. 1782) and Hannu Väisänen’s Schillmark Variations (2021), this study considers how woven textiles, like paintings, capture layers of time and unveil transnational textiles. By viewing woven textiles as material entanglements rather than mere objects, items or representations, we gain a deeper understanding of their role in shaping textile design histories. Woven textiles actively convey and shape knowledge, and cultural memory. Can textiles, like music, painting, sculpture, and architecture, serve as a universal cultural expression that transcends language, nationality, and borders? Examining northern Finnish textile traditions, particularly in a city of Tornio, by the border to Sweden in Finnish Lapland, and Pechenga (Petsamo in Finnish), a historically significant Arctic region on the coast of the Arctic Ocean, reveal the rich entanglement of trade, migration, and international influences. Inspired by Nils Schillmark’s Strawberry Girl (c. 1782) and Hannu Väisänen’s Schillmark Variations (2021), this study considers how woven textiles, like paintings, capture layers of time and unveil transnational textiles. By viewing woven textiles as material entanglements rather than mere objects, items or representations, we gain a deeper understanding of their role in shaping textile design histories. Woven textiles actively convey and shape knowledge, and cultural memory.